Strategic Implementation of Sharia Cooperative in Islamic Senior High Schools - Ashuri, Bahruddin; Hendri, Zul; Ishak, Khodijah (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
Sharia cooperatives in educational institutions represent an important instrument for strengthening economic empowerment, financial literacy, and Islamic ethical values among students. This study aims to analyze the strategic implementation of a sharia cooperative at Madrasah Aliyah Negeri (MAN) 1 Bengkalis by examining managerial preparation, institutional governance, sharia compliance, and operational practices. Using a qualitative descriptive approach, this research collected data through interviews, observations, and document analysis. The findings reveal that the implementation strategy includes establishing a strong institutional structure, applying sharia-based contracts such as murabahah and mudharabah, enhancing financial literacy programs, and developing member-oriented services. However, challenges remain, including limited human resource competence, low understanding of sharia contracts, and the absence of structured sharia supervision. The study recommends strengthening governance, integrating sharia cooperative education into the school curriculum, expanding digital service innovations, and involving a Sharia Supervisory Board (DPS). The results contribute to the literature on Islamic microfinance within educational settings and offer practical guidance for strengthening school-based sharia cooperatives.